2022
DOI: 10.28991/esj-2022-06-06-019
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development of Rural Teachers Based on Digital Literacy

Abstract: This research focuses on the professional development of teachers in rural areas based on digital literacy. It aims to measure the existing digital literacy and competence of rural teachers in Indonesia, Russia, and the Middle East and to assess the extent of digital literacy training provided to rural teachers for their professional development in these regions. In pursuit of this objective, a quantitative research method was incorporated into the study. The survey was conducted specifically for the research,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Despite the fact that it was found that students in rural areas have digital literacy that is in the low category. This is caused by several factors, the main factor being the limited access to digital resources and infrastructure in rural areas, especially in the use of the learning media (Dube, 2020;Ntaila & Mbaraka, 2023;Soekamto et al, 2022). Educational institutions in rural areas also experience limited technology and digital applications needed as learning media, which can hinder the integration of digital literacy into the biology curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that it was found that students in rural areas have digital literacy that is in the low category. This is caused by several factors, the main factor being the limited access to digital resources and infrastructure in rural areas, especially in the use of the learning media (Dube, 2020;Ntaila & Mbaraka, 2023;Soekamto et al, 2022). Educational institutions in rural areas also experience limited technology and digital applications needed as learning media, which can hinder the integration of digital literacy into the biology curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of digital literacy in rural areas is influenced by various factors (Acilar & Saebø, 2021;Tytova & Mereniuk, 2022). One of the main challenges is the lack of adequate digital infrastructure, which hinders the integration of digital literacy in these areas against basic competencies (Soekamto, Nikolaeva, Abbood, Grachev, Kosov, Yumashev et al, 2022;Yuliana, Hermawan, Prayitno, Ratih, Adhantoro, Hidayati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Cognitive Theory of Multimedia Learning [77], instructional materials with high-quality content and appropriate multimedia elements can enhance learners' cognitive processing and information retention. Engaging and interactive multimedia elements, such as videos, graphics, animations, and simulations, can facilitate the understanding of complex concepts, promote active learning, and increase learners' motivation [78,79]. Research has consistently shown that learners perceive highquality content as more relevant, credible, and valuable, leading to higher levels of engagement and the intention to participate in e-learning activities.…”
Section: -Findings and Discussionmentioning
confidence: 99%
“…Readiness relates to employees' initial support for digital transformation from perception to action. Since then, employee readiness has been considered an essential capability for establishing a sustainable and impactful digital transformation (Soekamto et al, 2022; Kurniady…”
Section: Introductionmentioning
confidence: 99%